Determinants of continuance intention to use mobile self-scanning applications in retail - Ferreira, A.; Silva, G. M.; Dias, Á. (International Journal of Quality and Reliability Management, 2023)
Retailers are increasingly using self-service technologies to improve customer experience and reduce costs. The purpose of this study is to identify factors that could explain the level of continuance intention of mobile self-scanning applications in retail. Based on previous theoretical streams, the present study integrates technology readiness (TR) and service quality into the technology acceptance model (TAM). Using data collected through an online survey of 217 users of a mobile self-scanning application of a large supermarket chain operating in Portugal, the study uses partial least squares structural equation modeling to test the proposed hypotheses. The results indicate that the continuance usage of the self-scanning Apps is directly driven by users’ satisfaction, and perceived usefulness. Findings also show that technology readiness has a positive and significant impact on ease of use and perceived usefulness. Ease of use has a positive impact on users’ satisfaction and perceived usefulness but has no direct effect on the continuance intention to use the application. Perceived quality has a positive direct effect on satisfaction, and a positive indirect effect on continuance intention. Finally, need for interaction has a negative effect on technological readiness. This work contributes to a better understanding of the emerging market for mobile self-scanning applications in retail applications, particularly relevant in a digital transition context.